Financial development and total factors productivity channel: Evidence from Africa - EZZAHID, Elhadj; ELOUAOURTI, Zakaria (The Indonesian Capital Market Review, 2018)
We discuss the link between financial development and economic growth through Total Factor Productivity (TFP) canal in African economies. First, we use a composite index to hierarchize financial development in 40 African countries. Then, we study this relationship by using the methodology of panel data based on the Breusch-Pagan LM Test and Hausman Test, to determine the nature of the specific effect, in a panel of 22 economies. The main results of our study show that the development of the financial sector does not promote total factors productivity in low-income and upper-middle-income countries. For the lower middle-income countries, the Finance-TFP relation- ship is significantly positive. The reforms of African financial systems should be designed and directed to increase the adequacy of financial services with the needs of each economy.